2002
DOI: 10.1046/j.1570-7458.2002.00997.x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of different plant nutrient regimes on the aphid Macrosiphum euphorbiae growing on petunia

Abstract: Three experiments were conducted to study how nutrient content of the host plant, Petunia axillaris hybrida Villm. Grandiflora Group, affects the performance of Macrosiphum euphorbiae (Thomas) (Homoptera: Aphididae). Aphid performance was analysed in relation to plant nutrient levels and the ratio of nitrogen to potassium (N/K). Phosphorus (P) had a positive effect on several parameters of aphid performance. Both P and K were associated with a short development time but a strong correlation between P and K con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
24
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(27 citation statements)
references
References 18 publications
3
24
0
Order By: Relevance
“…Mineral concentrations above optimum thresholds are usually toxic to aphids, e. g., high boron and molybdenum (AUCLAIR and SRIVASTAVA, 1972), phosphorus and potassium (AUCLAIR, 1965) to A. pisum;magnesium to A. pisum (AUCLAIR, 1965) and M. persicae (DADD and MITTLER, 1965) and nitrate to S. graminum (SALAS et al, 1990) The concentration of individual minerals (e.g., P, Mg, S), also their ratios in alfalfa tissues, was negatively correlated to aphid population variation in the present work, suggesting that they affected aphid biology. JANSSON and EKBOM (2002) found negative correlations between both magnesium and sulfur concentration in Petunia leaves and fecundity and longevity of the aphid Macrosiphum euphorbiae and BUSCH and PHELAN (1999) found that high phosphorus concentrations in soybeans resulted in longer developmental time of soybean looper (Pseudoplusia includens) and mineral proportions, such as high P:S ratio decreased pupal mass of this insect, but the opposite response was measured with a high S: P ratio.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Mineral concentrations above optimum thresholds are usually toxic to aphids, e. g., high boron and molybdenum (AUCLAIR and SRIVASTAVA, 1972), phosphorus and potassium (AUCLAIR, 1965) to A. pisum;magnesium to A. pisum (AUCLAIR, 1965) and M. persicae (DADD and MITTLER, 1965) and nitrate to S. graminum (SALAS et al, 1990) The concentration of individual minerals (e.g., P, Mg, S), also their ratios in alfalfa tissues, was negatively correlated to aphid population variation in the present work, suggesting that they affected aphid biology. JANSSON and EKBOM (2002) found negative correlations between both magnesium and sulfur concentration in Petunia leaves and fecundity and longevity of the aphid Macrosiphum euphorbiae and BUSCH and PHELAN (1999) found that high phosphorus concentrations in soybeans resulted in longer developmental time of soybean looper (Pseudoplusia includens) and mineral proportions, such as high P:S ratio decreased pupal mass of this insect, but the opposite response was measured with a high S: P ratio.…”
Section: Discussionmentioning
confidence: 97%
“…A decline on the performance of the aphids M. euphorbiae and Myzus persicae was found on potato tuber-filling leaves with a high C:N ratio, but C:N ratio on leaves was not correlated to sugar: amino acid ratio (KARLEY et al, 2002). Although most sucking insects respond positively to N fertilization (JANSSON and EKBOM, 2002), after reviewing several papers on N supplementation, VAN EMDEN (1966) related that in 36% of the cases aphids responded negatively to N fertilization, e.g., on barley (SALAS et al, 1990) and Polygonum pensilvanicum (MALBRY et al, 1997). SALAS et al (1990) related nitrogen supplementation was positively related to alkaloid (gramine) concentration and was negatively correlated to aphid (Schizaphis graminum) performance on barley.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…aphids) because of the low nitrogen content of phloem (0.004-0.06%) compared to other plant tissues (Mattson 1980). Numerous studies have shown that nitrogen fertilization of host plants results in increased growth rate, higher potential fecundity and shorter developmental time of aphids and ultimately increases their population density (Pettit et al 1994;Nevo and Coll 2001;Jansson and Ekbom 2002). However, many other studies have shown no or a negative response of aphids to nitrogen fertilization.…”
Section: Introductionmentioning
confidence: 99%
“…An excess of nitrogen (N) or deficiency of potassium (K) can lead to higher accumulation of amino acids which in turn can cause higher attack rate by sucking insects (JANSSON & EKBOM, 2002). Also, plant phenology such as leaf position on plant canopy, plant age, leaf areas, and trichomes besides natural enemies and weather can influence population of A. gossypii (CHAU et al, 2005;338 Ciênc.…”
Section: Introductionmentioning
confidence: 99%